Queer transgressions : the choreographing of a male homosexual presence with reference to selected choreographers,Queer Transgressions: The choreographing of homosexual identity with reference to selected South African choreographers post 2000 - De Boer, Kyle Dylan (Rhodes University, Faculty of Humanities, Department of Drama, 2011)
Queer Transgressions: The choreographing of a male homosexual presence with reference to selected choreographers explores queer identity and in particular representations of a male homosexual presence in dance. Within the methodological framework of dance studies and queer theory I explore the "•self fashioning"– of my male homosexual presence in dance. This is achieved by critically deconstructing my choreographic process when making choreography. Therefore this thesis is informed by both academic research and my self-reflexive experience of choreography and dance performance. The deconstruction of my autobiography and choreographic process is discussed with reference to both international and South African queer choreographers. This means that by accounting for my own experiences and approaches toward representing a male homosexual presence in dance, I explore the history and engagements of other queer choreographers also creating such representations. I therefore examine the works of selected choreographers and chart the development of the representation of a male homosexual presence in dance. By exploring the choreographic process of other queer choreographers I identify choreographic tactics that queer choreographers are using when making work. From this point of departure I shift the focus away from international queer choreographers and provide insight into the choreographic processes of South African queer choreographers. By accounting for the works and choreographic processes of South African choreographers, I provide a context in which my choreographic explorations on the subject matter can take place. This choreographic exploration manifests itself through a self-reflexive/autobiographic account on the research and practice of my choreographic process. During my choreographic exploration I set the challenge to both engage with and explore further, established "•queering tactics. This is done with the intention to reveal and create representations of a male homosexual presence in dance.
Keywords: Queer theory; Gender identity in dance; Homosexuality in dance; Homosexuality and dance; Male homosexuality; Dance -- South Africa; Choreographers -- South Africa